The miR156‐SPL4 module predominantly regulates aerial axillary bud formation and controls shoot architecture. Issue 3 (6th September 2017) - Gou, Jiqing; Fu, Chunxiang; Liu, Sijia; Tang, Chaorong; Debnath, Smriti; Flanagan, Amy; Ge, Yaxin; Tang, Yuhong; Jiang, Qingzhen; Larson, Preston R.; Wen, Jiangqi; Wang, Zeng‐Yu
Summary: Grasses possess basal and aerial axillary buds. Previous studies have largely focused on basal bud (tiller) formation but scarcely touched on aerial buds, which may lead to aerial branch development. Genotypes with and without aerial buds were identified in switchgrass ( Panicum virgatum ), a dedicated bioenergy crop. Bud development was characterized using scanning electron microscopy. Microarray, RNA‐seq and quantitative reverse transcription polymerase chain reaction (RT‐qPCR) were used to identify regulators of bud formation. Gene function was characterized by down‐regulation and overexpression. Overexpression of miR156 induced aerial bud formation in switchgrass. Various analyses revealed that SQUAMOSA PROMOTER BINDING PROTEIN LIKE4 ( SPL4 ), one of the miR156 targets, directly regulated aerial axillary bud initiation. Down‐regulation of SPL4 promoted aerial bud formation and increased basal buds, while overexpression of SPL4 seriously suppressed bud formation and tillering. RNA‐seq and RT‐qPCR identified potential downstream genes of SPL4 . Unlike all previously reported genes acting as activators of basal bud initiation, SPL4 acts as a suppressor for the formation of both aerial and basal buds. The miR156 ‐ SPL4 module predominantly regulates aerial bud initiation and partially controls basal bud formation. Genetic manipulation of SPL4 led to altered plant architecture with increased branching, enhanced regrowth after cutting and improved biomass yield.